2021
DOI: 10.3389/fphy.2021.729967
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Skyrmion Generation by Reflective Spin Wave Focusing

Abstract: We propose a method to generate magnetic skyrmions by focusing spin waves totally reflected by a curved film edge. The edge contour is derived to be parabolic and frequency-independent based on the identical magnonic path length principle. We performed micromagnetic simulations to verify our theoretical design. Under proper conditions, the reflected spin waves first converge at the focal point with the enhanced intensity leading to the emergence of magnetic droplets, which are then converted to magnetic skyrmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
0
4
0
3
Order By: Relevance
“…), 可以求得自旋波焦点的 位置坐标: (identical MPL principle), 可以反推出完美透镜 的界面形状 [37] . 假设一自旋波束水平入射至界面, 在界面另一侧聚焦于一点, 如图8(a)所示, 则等磁 的微磁模拟结果; (d)焦点坐标随自旋波频率的变化 [128] coordinates as a function of the spin-wave frequency [128] .…”
Section: 利用傍轴近似(unclassified
See 2 more Smart Citations
“…), 可以求得自旋波焦点的 位置坐标: (identical MPL principle), 可以反推出完美透镜 的界面形状 [37] . 假设一自旋波束水平入射至界面, 在界面另一侧聚焦于一点, 如图8(a)所示, 则等磁 的微磁模拟结果; (d)焦点坐标随自旋波频率的变化 [128] coordinates as a function of the spin-wave frequency [128] .…”
Section: 利用傍轴近似(unclassified
“…最近研究表明DMI可以打破两种极化自旋波 模式的简并 [60,61] , 为实现磁子SG效应提供了可能. (c) the process of the skyrmion generated by the spin-wave focusing [37] .…”
Section: 磁子的斯特恩-盖拉赫效应unclassified
See 1 more Smart Citation
“…Despite substantial success in terms of skyrmion nucleation using a number of di erent approaches, as mentioned above, the use of the SWs and spin dynamics for skyrmion formation has not been widely explored [219][220][221]. However, such an e ect can be very interesting in magnonics.…”
Section: Nucleation and Stabilization Of Magnetic Skyrmions By Swsmentioning
confidence: 99%
“…However, such an e ect can be very interesting in magnonics. Recently, Yao et al [221] showed the method of generating magnetic skyrmions in the e ective Co layer with DMI and PMA by focusing SWs totally re ected by a curved lm edge. This study numerically demonstrated that the accumulation of SW energy in the focal spot can be su cient to form or destroy a skyrmion.…”
Section: Nucleation and Stabilization Of Magnetic Skyrmions By Swsmentioning
confidence: 99%